2017
DOI: 10.3892/ol.2017.5828
|View full text |Cite
|
Sign up to set email alerts
|

siRNA-mediated knockdown of ID1 disrupts Nanog- and Oct-4-mediated cancer stem cell-likeness and resistance to chemotherapy in gastric cancer cells

Abstract: Abstract. DNA-binding protein inhibitor ID-1 (ID1) serves an essential role in tumor progression, and the self-renewal and pluripotency of embryonic stem cells. However, the effect of ID1 on the stemness and cancer stem cell (CSC)-like properties of gastric adenocarcinoma cells remains to be elucidated. In the present study, effective ID1 knockdown was achieved in gastric cancer (GC) cells using small interfering RNA, and the self-renewal ability and cisplatin (DDP) sensitivity of GC cells was subsequently exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 49 publications
1
11
0
Order By: Relevance
“…The CSCs possess critical roles in gastric cancer initiation, progression, and recurrence associated with resistance to radio-and chemotherapy [18]. In the present study, we showed that PRR11 was highly expressed in a subpopulation of gastric cancer cells with stem-like characteristics, and sat at the center of a signaling network, since changes in its expression pattern could drastically alter the biology properties of gastric CSCs and non-CSCs.…”
Section: Discussionmentioning
confidence: 71%
“…The CSCs possess critical roles in gastric cancer initiation, progression, and recurrence associated with resistance to radio-and chemotherapy [18]. In the present study, we showed that PRR11 was highly expressed in a subpopulation of gastric cancer cells with stem-like characteristics, and sat at the center of a signaling network, since changes in its expression pattern could drastically alter the biology properties of gastric CSCs and non-CSCs.…”
Section: Discussionmentioning
confidence: 71%
“…ID-1 plays a number of key roles in cellular differentiation, cell cycle progression, tumorigenesis and metastasis (18). ID-1 predominantly acts as an oncogene in several types of tumor, including gastric (19), pancreatic (20), colorectal (21) and lung cancer (22). Furthermore, a previous study demonstrated that higher protein levels of ID-1 are associated with tumor recurrence and lymph node metastasis in patients with OSCC (11).…”
Section: Discussionmentioning
confidence: 99%
“…Certain members of the homeobox superfamily have been implicated in normal development as well as in the pathological development of cancer. OCT-4 is a homeobox gene well known for its function in generating induced pluripotent stem cells (Bhartiya, 2013;Seiler et al, 2011); this gene has also been identified as an oncogene known for promoting the features of cancer stem cells (Li et al, 2017;Phiboonchaiyanan & Chanvorachote, 2017). In addition to OCT-4, an increasing body of evidence reveals that homeobox genes may participate in the promotion of various malignant phenotypes such as the proliferation, migration and invasion of cancers (Hirao et al, 2019;Miwa & Kanda, 2019;Rodini et al, 2012;Song et al, 2019).…”
Section: Discussionmentioning
confidence: 99%